Pengaruh Penambahan Limbah Kertas 80% dan Kayu 20% Sebagai Alternatif Media Tanam Jamur Tiram Putih (Pleurotus ostreatus) - Isnawati, I; Mahmudi, Irkham; Khayati, Dian N; Utami, Tri W; Purwanti, Kiki E; Ulfa, Maria (Bioma : Berkala Ilmiah Biologi, 2019)
Paper waste is anÂ  organic residual that has not been widely utilized and its existence around us. The high cellulose content in paper waste allows it to be used as a media for cultivating white oyster mushrooms. This aims to compare the speed of mycelium propagation from different concentration of paper in each growing medium. The study used a Completely Randomized Design (CRD) with six treatments and five repeattation. The treatment used is the difference in the composition of 0% paper waste media (control); 20% of paper waste; 40% of paper waste; 60% of paper waste; 80% of paper waste; and 100% of waste paper. The data were obtained from six timeÂ  observations in the form of mycelium propagation (cm)and tested with anava. The results were not significant at 1,65 using correcttion factor 2,53. Mycelium propagation speed was influenced by environmental factors such as temperature, light intensity, humidity, and air circulation.